2022
DOI: 10.1111/jmft.12589
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barriers to couples therapy

Abstract: What prevents couples from entering therapy? Given that the rate of couple help‐seeking is low, we need a better understanding of barriers to couple help‐seeking. To expand our understanding of these barriers, we asked almost 300 people who expressed an interest in couples therapy, to clarify what kept them from seeking help. A content analysis of participant's responses found six distinctive categories: cost of treatment, logistics, the modality of treatment, trustworthiness, relational factors, and a clear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The intake coordinators are not able to determine if an individual diagnosis that could be reimbursable for couple therapy is present, and thus default to indicating that it must be paid out-of-pocket. A recent study found the cost of treatment to be one of the most frequently identified barriers to couple therapy by clients (Hubbard & Anderson, 2022). As participants in our study identified, offering couple therapy only as an out-of-pocket paid service creates barriers for many couples seeking help who cannot afford to pay for conjoint therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intake coordinators are not able to determine if an individual diagnosis that could be reimbursable for couple therapy is present, and thus default to indicating that it must be paid out-of-pocket. A recent study found the cost of treatment to be one of the most frequently identified barriers to couple therapy by clients (Hubbard & Anderson, 2022). As participants in our study identified, offering couple therapy only as an out-of-pocket paid service creates barriers for many couples seeking help who cannot afford to pay for conjoint therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, couple therapy may or may not be covered by insurance for a given case, as the diagnostic codes of relational issues are rarely listed as reimbursable procedures (Clawson et al, 2018). Thus, despite the clear evidence of the effectiveness and cost-effectiveness of couple therapy, barriers exist that prevent adequate reimbursement (Asfaw et al, 2020; Russell Crane & Payne, 2011), which thereby contribute significant barriers to the provision of couple therapy services (Hubbard & Anderson, 2022) and further exacerbate public health concerns by limiting access to effective treatments (e.g., Barbato & D’Avanzo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given that couples therapy, the environment where relationship patterns are typically invoked, is difficult to access for many people, it is imperative, from a public health perspective, to create and test mechanisms that can be built into accessible and effective online interventions (Hubbard & Anderson, 2022;Johnson et al, 2002). Relationship health affects not just partners, but children as well, suggesting that increases in relationship health can have positive health impacts for the entire family and societal system (APA, n.d.).…”
Section: The Current Studymentioning
confidence: 99%
“…Interventions delivered via telephone and text messaging can reach even more individuals. Indeed, these accessibility and cost benefits of delivering care to dyads through their digital devices could address about half of the identified major barriers to distressed couples seeking couple therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%